The energetics and benefit of an arm swing in submaximal and maximal vertical jump performance - Lees, A.; Vanrenterghem, J.; de Clercq, D. (Journal of Sports Sciences, 2006)
The aims of this study were to investigate the energy build-up and dissipation mechanisms associated with using an arm swing in submaximal and maximal vertical jumping and to establish the energy benefit of this arm swing. Twenty adult males were asked to perform a series of submaximal and maximal vertical jumps while using an arm swing. Force, motion and electromyographic data were recorded during each performance and used to compute a range of kinematic and kinetic variables, including ankle, knee, hip, shoulder and elbow joint powers and work done. It was found that the energy benefit of using an arm swing appears to be closely related to the maximum kinetic energy of the arms during their downswing, and increases as jump height increases. As jump height increases, energy in the arms is built up by a greater range of motion at the shoulder and greater effort of the shoulder and elbow muscles but, as jump height approaches maximum, these sources are supplemented by energy supplied by the trunk due to its earlier extension in the movement. The kinetic energy developed by the arms is used to increase their potential energy at take-off but also to store and return energy from the lower limbs and to "pull" on the rest of the body. These latter two mechanisms become more important as jump height increases with the pull being the more important of the two. We conclude that an arm swing contributes to jump performance in submaximal as well as maximal jumping but the energy generation and dissipation sources change as performance approaches maximum.